Pengaruh Program Sales Promotion dan Harga Terhadap Keputusan Pembelian Makanan dan Minuman Coffee Shop Kolusi Coffee di Kota Bekasi (Survey pada Konsumen Coffee Shop Kolusi Coffee di Bekasi) - Rifdah 'Aafiyatunnisa; Ratih Tresnati (Bandung Conference Series: Business and Management, 2022)
Abstract. The purpose of this study is to find out the implementation of the Sales Promotion Program, Prices and Purchasing Decisions on food and beverages at the Kolusi Coffee coffee shop, as well as to find out how much influence the Sales Promotion Program partially and simultaneously has on purchasing decisions on food and beverages at the Coffee Shop Kolusi Coffee in Bekasi City. The problems found in this study are Sales Promotion and Price have not been able to drive Purchasing Decisions on Coffee Shop Kolusi Coffee food and beverages because a number of consumers do not have an interest in the sales promotion program offered and the prices offered are also quite expensive. The method used is a survey method with a sampling technique using a non-probability sampling technique, and the type of non-probability sampling technique chosen is a purposive sampling technique. This type of research is descriptive verifiability with a quantitative approach. The population in this study were consumers of the Kolusi Coffee coffee shop in Bekasi City. The sample taken was 100 respondents. The data analysis method used is a multiple linear regression analysis which aims to determine the direction of the relationship between independent variables, namely Sales Promotion (X1) and Price (X2) with the dependent variable, namely The Purchase Decision (Y). The results of this test state that Sales Promotion partially affects the Purchase Decision, while the Price does not partially affect the Purchase Decision. However, simultaneously the variables Sales Promotion and Price have a significant effect on purchasing decisions on food and beverages at the Kolusi Coffee Coffee Shop in Bekasi City. Abstrak. Tujuan penelitian ini untuk mengatahui penerapan Program Sales Promotion, Harga dan Keputusan Pembelian pada makanan dan minuman di coffee shop Kolusi Coffee, serta untuk mengetahui seberapa besar pengaruh Program Sales Promotion secara parsial dan simultan terhadap Keputusan Pembelian pada makanan dan minuman di Coffee Shop Kolusi Coffee di Kota Bekasi. Masalah yang ditemukan dalam penelitian ini yaitu Sales Promotion dan Harga belum mampu mendorong Keputusan Pembelian pada makanan dan minuman Coffee Shop Kolusi Coffee dikarenakan sejumlah konsumen tidak memiliki ketertarikan terhadap program sales promotion yang ditawarkan dan harga yang ditawarkan juga cukup mahal. Metode yang digunakan adalah metode survey dengan teknik pengambilan sampel menggunakan teknik non-probability sampling, dan jenis teknik non-probability sampling yang dipilih ialah teknik purposive sampling. Jenis penelitian inin adalah verifikatif deskriptif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah konsumen coffee shop Kolusi Coffee di Kota Bekasi. Sampel yang diambil adalah 100 orang responden. Metode analisis data yang digunakan adalah analisis regresi linier berganda yang yang bertujuan untuk mengetahui arah hubungan antara variabel independen yaitu Sales Promotion (X1) dan Harga (X2) dengan variabel dependen yaitu Keputusan Pembelian (Y). Hasil pengujian ini menyatakan bahwa secara Sales Promotion secara parsial berpengaruh signifikan terhadap Keputusan Pembelian, sedangkan Harga tidak berpengaruh secara parsial terhadap Keputusan Pembelian. Namun secara simultan variabel Sales Promotion dan Harga berpengaruh signifikan terhadap Keputusan Pembelian pada makanan dan minuman di Coffee Shop Kolusi Coffee di Kota Bekasi.